Tricholoma colposii (Tricholomataceae, Basidiomycota), a new edible species of matsutake fungi from Eastern Mexico with economic and biocultural importance - Ayala-Vásquez, Olivia; Martínez-Reyes, Magdalena; Isaac De La Fuente, Javier; Martínez-González, César Ramiro; Flores Armas, Leticia; Hernández-Santiago, Faustino; Pérez-Moreno, Jesús (Phytotaxa, 2022)
Matsutake fungi include a complex of edible mushrooms highly prized worldwide, particularly in Japan where they are considered one of the most luxurious ingredients. These species establish ectomycorrhizal symbioses with angiosperms and gymnosperms in the Northern Hemisphere and in North America only three species are currently known. In the present contribution a fourth species of this geographical area is described, Tricholoma colposii sp. nov. is described from Veracruz state, in eastern Mexico based on morphological and molecular (nrITS) data. This species is characterized by middle size basidiomata, with orange brown to brown pileus and stipe, squamose when young and with appressed scales in maturity, cylindric, fibrillous to scaly stipe, with globose to ellipsoid (4.5–)5–6 (–7) × (3–) 4–5 (–6) μm smooth spores, sporomes with sweet fruit odor and raw green bean flavour. The species grows associated with Pinus teocote forests. The macro- and micromorphological characters in conjunction with the nrITS-based phylogenetic analysis using Maximum Likelihood method and Bayesian inference support the proposal of this new species of Mexican matsutake. Detailed descriptions, photographs and comparisons with phenetic and phylogenetic related species are presented.